Inhibitory effect of Buah Merah oil on melanogenesis via degradation of tyrosinase - Mayuko Hatai; Hisae Yoshitomi; Toshiaki Nishigaki; Ming Gao (Balai Besar Industri Agro, 2018)
Buah Merah (Pandanus conoideus) is exclusively distributed in Papua island and its neighboring areas. The extract oil from fruits (Buah Merah oil) contains rich in lipids, carotenoids and vitamin E.We assessed the effects of Buah Merah oil on melanogenesis in B16 melanoma cells. In the presence of alpha-melanocyte stimulating hormone (α-MSH), B16 melanoma cells are stimulated to enhance melanin synthesis. Buah Merah oil inhibited α-MSH-induced melanin synthesis with no cytotoxicity. This decrease in melanogenesis was correlated with reduced enzyme activity and decreased protein expression levels of tyrosinase. Tyrosinase is a type 1 membrane glycoprotein that is the critical rate-limiting enzyme involved in melanin synthesis. Furthermore, the Buah Merah oil-induced decrease in melanin content was accompanied by a decrease in the amount and activity of tyrosinase whereas the mRNA level of tyrosinase was unchanged. Moreover, treatment with proteasome inhibitor MG132 blocked the down-regulation of melanogenesis by Buah Merah oil. Immunoprecipitation analysis also revealed that treatment with Buah Merah oil modulated the ubiquitination of tyrosinase, that is Buah Merah oil increased the amount of ubiquitinated tyrosinase.Taken together, the present results indicate that the depigmenting effect of Buah Merah oil might be due to inhibition of tyrosinase expression through the ubiquitin proteasome-mediated degradation of tyrosinase.